2022
DOI: 10.1021/acspolymersau.2c00047
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Activation Experiments Reveal Significantly Different Mechanochemical Reactivity of Furan–Maleimide and Anthracene–Maleimide Mechanophores

Abstract: During the past two decades, our understanding of mechanochemical reactivity has advanced considerably. Nevertheless, an incomplete knowledge of structure–activity relationships and the principles that govern mechanochemical transformations limits molecular design. The experimental development of mechanophores has thus benefited from simple computational tools like CoGEF, from which quantitative metrics like rupture force can be extracted to estimate reactivity. Furan–maleimide (FM) and anthracene–maleimide (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Mechanical force promotes a variety of chemical transformations including formal retro-cycloaddition reactions, electrocyclic ring-opening reactions, homolytic , and heterolytic bond scission, and metal–ligand dissociation. , Mechanochemical reactions have been harnessed for a wide range of applications including visual force sensing, catalyst activation, , conductivity switching, and molecular release . Fundamentally, understanding structure–mechanochemical activity relationships for mechanically sensitive moieties (i.e., mechanophores) is critical for informing the rational design of new stimuli-responsive materials and their emergent applications …”
mentioning
confidence: 99%
“…Mechanical force promotes a variety of chemical transformations including formal retro-cycloaddition reactions, electrocyclic ring-opening reactions, homolytic , and heterolytic bond scission, and metal–ligand dissociation. , Mechanochemical reactions have been harnessed for a wide range of applications including visual force sensing, catalyst activation, , conductivity switching, and molecular release . Fundamentally, understanding structure–mechanochemical activity relationships for mechanically sensitive moieties (i.e., mechanophores) is critical for informing the rational design of new stimuli-responsive materials and their emergent applications …”
mentioning
confidence: 99%
“…13 The retro Diels−Alder (RDA) reaction involving furan and maleimide has emerged as a popular scaffold in the landscape of polymer mechanochemistry. 14,15 Several studies have been performed on this particular mechanophore for its dynamical covalent bonds that are longer and weaker than most typical covalent bonds. This makes them kinetically facile to use for mechanochemistry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Craig and co-workers characterized the mechanochemically active domain in gem -dihalocyclopropane ( g DHC) functionalized polybutadiene and later reported that the ring opening in g DHCs occur because of strain under mechanical compression and tension. , Diesendruck et al developed a mechanophore capable of releasing acid when subjected to mechanical stress, also serving as a cross-linker in poly­(methyl acrylate) (PMA) . The retro Diels–Alder (RDA) reaction involving furan and maleimide has emerged as a popular scaffold in the landscape of polymer mechanochemistry. , Several studies have been performed on this particular mechanophore for its dynamical covalent bonds that are longer and weaker than most typical covalent bonds. This makes them kinetically facile to use for mechanochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In the pursuit of such biomimetic functions, recently synthetic chemists have developed materials that show response to the mechanical force, often referred to as mechanoresponsive materials and a subclass of these systems that show force-induced optical changes is termed mechanochromic materials. The preparation of such materials and investigation of their properties have been of increasing interest in the last decades owing to their sophisticated functions, such as strengthening of mechanical properties, change of optical behavior, and the emergence of chemiluminescence. To achieve such material, a mechanoresponsive unit can be integrated into polymer networks to have a broader scope of their utility. Over the past few years, a large variety of synthetic small molecules have been used as mechanoresponsive units. ,, While the introduction of some of these units in polymer resists any kind of mechanical deformation, the other majority exhibit mechanochromic behavior through irreversible covalent bond rupture beyond a certain threshold, thus, limiting their practical utility. Since activation of their mechanochromic behavior relies on the rupture of one or more covalent bonds, this method is typically energy-demanding.…”
Section: Introductionmentioning
confidence: 99%